Inhibition of Multi Drug-Resistant (MDR) Escherichia coli and Klebsiella pneumoniae by bacteriocin bifidobacteria and the viability of selected bifidobacteria encapsulated with tapioca - OEDJIJONO OEDJIJONO; DYAH FITRI KUSHARYATI; DINI RYANDINI; HENDRO PRAMONO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Oedjijono, Kusharyati DF, Ryandini D, Pramono H. 2023. Inhibition of Multi Drug-Resistant (MDR) Escherichia coli and Klebsiella pneumoniae by bacteriocin bifidobacteria and the viability of selected bifidobacteria encapsulated with tapioca. Biodiversitas 24: 4175-4182. This study was conducted to investigate the antimicrobial efficacy of eight Bifidobacterium spp. against multidrug-resistant (MDR) bacteria, namely Escherichia coli and Klebsiella pneumoniae. Additionally, the viability of selected encapsulated bifidobacteria was assessed at different storage durations. The non-neutralized or neutralized supernatant pH of eight bifidobacterial isolates (BCC6, BC4, BBP6, BC7, BBP1, BC13, BCC5, BCC8) inhibited the growth of MDR E. coli and K. pneumoniae. The non-neutralized supernatant Bifidobacterium sp. BBP6 resulted in the highest inhibition against E. coli or K. pneumoniae with a clear zone of 8 mm. In contrast, the neutralized supernatant of Bifidobacterium sp. BBP1 showed the highest inhibition only against E. coli, with a clear zone of 8 mm. The bacteriocin of BCC5 and BBP6 isolates showed the highest inhibition against MDR E. coli, with inhibition zones of 12.5 mm and 12 mm, respectively. Similarly, the bacteriocin of BBP6 isolate gave the highest inhibition against K. pneumoniae, with a zone of 7 mm. The cell numbers of the tapioca-encapsulated isolate BBP6 were quite stable in comparison to BBP1, which were 8.4 log cfu.g-1 and 8.1 log cfu.g-1 at initial storage and 6.32 log cfu.g-1 and 7.41 log cfu.g-1 after eight weeks. The viability percentage of encapsulated Bifidobacterium sp. BBP6 (86.91%) surpassed that of BBP1 isolate (78.41%) during the eight-week storage period at 4oC. The storage time of the BBP6 at 4oC was 6.05 weeks or 42.35 days.